2015
DOI: 10.1007/s10886-015-0630-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of age and Reproductive Status on Tergal Gland Secretions in Queenless Honey bee Workers, Apis mellifera scutellata and A. m. capensis

Abstract: Secretions from tergal glands are part of a queen's pheromonal control of worker reproduction in honey bees. However, in queenless honey bee colonies, workers compete to gain pheromonal, and hence reproductive dominance, over nestmates with ontogenetic changes in their glandular secretions that affect the behavioral or physiological responses of other individuals. Using gas chromatography/mass spectrometry, we investigated for the first time the age-dependent changes in tergal gland secretions of queenless wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 45 publications
0
29
0
Order By: Relevance
“…These three esters (ethyl palmitate, ethyl oleate and ethyl stearate) have not been previously reported in tergal gland profiles of either queens or workers (Espelie et al 1990;Smith et al 1993;Wossler and Crewe 1999a) but were recently reported in tergal gland secretions of workers (Okosun et al 2015). While, the exact functions of these tergal gland components as either primer or releaser pheromones are not known in workers, the queen's tergal gland extracts elicited attraction of drones and workers, as well as suppressed ovarian activation in workers De Hazan et al 1989;Brockmann et al 2006;Wossler and Crewe 1999b, c).…”
Section: Introductionmentioning
confidence: 70%
See 4 more Smart Citations
“…These three esters (ethyl palmitate, ethyl oleate and ethyl stearate) have not been previously reported in tergal gland profiles of either queens or workers (Espelie et al 1990;Smith et al 1993;Wossler and Crewe 1999a) but were recently reported in tergal gland secretions of workers (Okosun et al 2015). While, the exact functions of these tergal gland components as either primer or releaser pheromones are not known in workers, the queen's tergal gland extracts elicited attraction of drones and workers, as well as suppressed ovarian activation in workers De Hazan et al 1989;Brockmann et al 2006;Wossler and Crewe 1999b, c).…”
Section: Introductionmentioning
confidence: 70%
“…m . scutellata workers (palmitic acid, oleic acid, n -heneicosene and n -tricosene) and the three ethyl esters (ethyl palmitate, ethyl oleate and ethyl stearate) (Okosun et al 2015) were tested in this study. The average concentration of tergal glands secretions of one dominant A .…”
Section: Pseudo-queen Tergal Gland Blendmentioning
confidence: 99%
See 3 more Smart Citations